From Village Commons to Public Goods - Trémon, Anne-Christine (Berghahn Books, 2023)
Illuminating the complex processes of China’s uneven urbanization through the lens of the transition from village commons to public goods, this book is set in three urbanized villages in Shenzhen, Chengdu, and Xi’an, which have experienced similar demographic explosions and dramatic changes to their landscapes, the livelihoods of its inhabitants, and the power structures governing their residents. Graduated provision is the delivery of public goods informed by the teleological ideology of urbanization, and by neoliberalism with Chinese characteristics, and has been employed as an answer to the challenges of making public goods, such as welfare provisions, public parks, education, and senior care, equally accessible to all in recently urbanized communities.